Work-Related Stressors, Coping Strategies: Its Relation to Job Performance and Perceived Organizational Support among Critical Care Nurses - Mahdia M. E. Morsy; Shaimaa M. A. Ebraheem (Evidence-Based Nursing Research)
Context: Work-related stressors are a world phenomenon. It results in a variety of diseases or disorders in terms of physical, psychological, and behavioral. It is commonly associated with jobs that require a lot of direct interactions with clients such as nurses that could affect nurses' job performance and cause high costs for the hospital. A problem needs a sense of support from the organization.